Multifactor productivity, environmental change, and regulatory impacts in the U.S. West Coast groundfish trawl fishery, 1994–2013. (December 2015) - Mamula, Aaron; Collier, Trevor
Abstract: This paper provides estimates of multifactor productivity for vessels participating in the West Coast Limited Entry groundfish trawl fishery from 1994 to 2013. Impacts of regulatory change on productivity are examined and productivity dynamics are evaluated across spatial and behavioral dimensions. Results suggest four different periods of consistency: (i) a decline in productivity from 1994 to 2002, (ii) a sharp increase in productivity following a permit buyback in 2003, (iii) stagnant productivity from 2005 to 2010, and (iv) another increase in productivity following implementation of individual transferable quotas ("catch shares"). Important spatial differences in productivity are uncovered-vessels fishing south of 40 ° 10 ' N latitude were generally less productive than those fishing north of the same line. Additionally, the productivity gap between north and south was enlarged following the policy changes (buyback in 2003 and catch shares in 2011). Productivity from 1994 to 2013 tended to be higher among vessels that were more diversified in terms of their total portfolio of commercial fishing revenue. However, productivity tended to be lower among vessels whose targeting strategies were more diversified within the groundfish fishery. Highlights: Multifactor productivity was estimated for the U.S. West coast limited entry groundfish trawl fishery from 1994 to 2013. A decline in productivity was found from 1994 to 2002. Management interventions including a fisheries buyback in 2003 and catch shares in 2011 were found to enhance vessel productivity. Productivity was found to vary across regions even after accounting for environmental and behavioral factors.